2002
DOI: 10.1002/nme.574
|View full text |Cite
|
Sign up to set email alerts
|

A vertex‐based finite volume method applied to non‐linear material problems in computational solid mechanics

Abstract: INTRODUCTIONOver the last three decades the FE method has firmly established itself as the standard approach for problems in computational solid mechanics (CSM), especially with regard to deformation problems involving non-linear material analysis [1,2]. As a contemporary, the FV method has similarly established itself within the field of computational fluid dynamics (CFD) [3,4]. Both classes of methods integrate governing equations over pre-defined control volumes [3,5], which are associated with the elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…The use of a mixed approach proved to be very efficient in large strain solid dynamics, circumventing the above-mentioned drawbacks for the traditional displacement based techniques. Early attempts at applying CFD-like numerical techniques in the context of displacement based computational solid dynamics are reported in references [2,[43][44][45][46][47][48]. Eulerian Finite Volume Godunov methods, typically used for modelling compressible gas dynamics, were employed to model plastic flows in solid dynamics [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a mixed approach proved to be very efficient in large strain solid dynamics, circumventing the above-mentioned drawbacks for the traditional displacement based techniques. Early attempts at applying CFD-like numerical techniques in the context of displacement based computational solid dynamics are reported in references [2,[43][44][45][46][47][48]. Eulerian Finite Volume Godunov methods, typically used for modelling compressible gas dynamics, were employed to model plastic flows in solid dynamics [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…This distance d(i s ) is non-dimensionalized by the maximum value d max of all the d(i s ). The deformation of the fluid node is calculated as the product of a distance function f(i s ) and the deformation of its associated wall node : (18) The distant function is constructed using two exponential damping functions as: (19) where The distance function Eq. (19) approaches 1 when d goes to 0 and the function approaches 0 when d goes to d max .…”
Section: Dynamic Mesh Methods and Coupling Algorithmmentioning
confidence: 99%
“…Wheel [17] even showed that the FV method achieves greater accuracy than the FE method for a benchmark problem in selected test cases. The implementation of FV methods for CSD computations can be classified into two categories: the cell-centered approach [9,10,12,14,17] and the cell-vertex approach [1,13,15,16,18]. Both approaches are locally and globally conservative.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the spatial discretization of equation utilized here and its evaluation of on a range of benchmarks may be found in a number of references; see, for example, Bailey and Cross [45], Taylor et al [46] and Slone et al [47].…”
Section: The Structural Solvermentioning
confidence: 99%